Предмет: Алгебра,
автор: Golubeva82525
Решите, срочно, очень нужно
Приложения:
![](https://files.topotvet.com/i/a91/a918eb3d10390f775577eea087578e63.jpg)
Ответы
Автор ответа:
0
возводим обе части в квадрат
(2х+3)(7-х)=(х+3)^2
14х+21-2х^2-3х=х^2+6х+9
-2х^2-х^2+14х-3х-6х+21-9=0
-3х^2+5х+12=0
D=b^2-4ac
D=25+144=169(корень 13)
x1=(-5+13)/-6=-8/6
х2=(-5-13)/-6=3
(2х+3)(7-х)=(х+3)^2
14х+21-2х^2-3х=х^2+6х+9
-2х^2-х^2+14х-3х-6х+21-9=0
-3х^2+5х+12=0
D=b^2-4ac
D=25+144=169(корень 13)
x1=(-5+13)/-6=-8/6
х2=(-5-13)/-6=3
Похожие вопросы
Предмет: Химия,
автор: safarovelmir82
Предмет: Геометрия,
автор: akubroman94
Предмет: Информатика,
автор: Аноним
Предмет: Математика,
автор: gaynelyanov07
Предмет: Математика,
автор: умница54